Online services of commercial banks towards customer loyalty in Bangladesh - Uddin, Bashir; Haque, Ahasanul; Nayeem, Abdur Rakib; Maruf, Tarekol Islam (Future Academy, 2018)
It has become a common phenomenon in these days; a lot of Bangladeshi people are relaying on using online banking services and it has gained much credibility. For capturing market, focusing and attracting the potential clients and keeping prevailing clients, there are many initiatives are being taken by many financial and banking organizations. As the electronic banking customers heavily rely on internet base banking services that influence the banking policy makers to take more electronic banking services promoting initiative for current and potential customers in competitive banking market in Bangladesh. There is no significant research oriented work has not been yet, in Bangladesh though clients reliance and customer confident in online services are integrated part of internet banking. The statistical evidence may play an identical implication for retaining customer’s trust on electronic banking services in Bangladesh. A total of 250 respondents have been chosen from different government-owned and public banks following convenient sampling technique. While exploratory analysis has been used to fit the right items for each construct, structural modeling technique has been applied to assess the relationship between and among the constructs. From this revision it is observed that online services in the commercial banking sectors in Bangladesh have an impact towards loyalty of the customers. The research findings will be useful to the commercial banks of Bangladesh. Clients, bankers, managers, researchers, academicians will definitely be benefited from the present study.